Varia. Irigarai familiaren funtsa Nafarroako Errege Artxibo Nagusian: katalogoa - Santazilia, Ekaitz (Fontes linguae vasconum, 2022)
Recently, the Royal and General Archive of Navarre has received Fermin Irigaray’s and Angel Irigaray’s collection of documents as a donation. The collection reflects the outstanding contribution these two men (father and son) made in the 20th century in favour of the Basque language. Among others, it includes old texts, manuscripts, articles, press, journals, books, drafts, and notebooks, starting from the 17th century and, mostly to the 19th and 20th centuries. Since it is an interesting material to study the history of the Basque language, Fontes Linguae Vasconum will publish the cathalogue of the documentation in two parts. This first part includes published documents.